Effect of Maintenance at Different Salinity against White Spot Syndrome Virus (WSSV) Infection Level in Post Larvae Litopenaeus vannamei Shrimp - Amrillah, Attabik Mukhammad; Widyarti, Sri; Kilawati, Yuni (The Journal of Experimental Life Science, 2015)
White spot syndrime virus (WSSV) is a highly contagious disease in shrimp culture and causing 100% death within 3-10 days of clinical symptoms. WSSV can infect shrimp in post larvae stage (PL) to a size of 40 g. This study was aimed to determine the effect of different salinity against WSSV infection level in post larvae vannamei shrimp (Litopenaeus vannamei). In this study PL 40 size of vannamei shrimp infected with WSSV in virus concentration 20 μg.mL-1 in three different salinity is 5 ppt, 15 ppt, 25 ppt for 4 hours using the soaking method then maintened for 7 days post-infection and then infection level and water quality observed. Data analysis used simple linear regression and F test with a confidence level 95% (P <0.05). The results indicate changes in behavior between healthy and infected shrimp in three levels (mild, moderate, severe). The highest total mild infection in salinity treatment of 25 ppt by 30%, the highest total medium infection at salinity treatment 25 ppt by 37%, the highest total severe infection at salinity treatment 5 ppt by 57%. Shrimp that have mild level of infection are increasing in concominant higher salinity, while the severe infection level has decreases with increasing salinity. Keywords: Infection Level, Litopenaeus vannamei, Post Larvae, Salinity, WSSV